Inovação sustentável em micro e pequenas empresas: estudo de caso em uma confecção de roupas - Talita Venilda Guimarães (2023)
Innovation is traditionally seen as a competitive advantage, also in micro and small companies. The 20th century was marked by an acceleration of innovation processes, but also by the progressive deterioration of the environment and the prospect of scarcity of natural resources, increasing concern with environmental issues, both by citizens and by the public authorities, bringing these issues to the daily lives of companies. This paper seeks to discuss the conditions for sustainable innovation in small Brazilian apparel companies, a sector that is notably problematic, whether in environmental, social or economic terms. The work was carried out from a case study centered on a clothing factory located in the region of Itabirito (MG). The objective was the proposition of principles aimed at introducing innovations that guarantee the company's sustainability. Thus, environmental practices can generate value for the company, as well as benefit employees, the community and the environment, making it competitive in the market in which it operates. As a result, process and product improvements were proposed with the aim of making the company under study sustainable.